Fluoride bioavailability in saliva and plaque - Naumova, Ella A; Kuehnl, Phillip; Hertenstein, Philipp; Markovic, Ljubisa; Jordan, Rainer A; Gaengler, Peter; Arnold, Wolfgang H (BMC oral health, 2012)
Background Different fluoride formulations may have different effects on caries prevention. It was the aim of this clinical study to assess the fluoride content, provided by NaF compared to amine fluoride, in saliva and plaque. Methods Eight trained volunteers brushed their teeth in the morning for 3 minutes with either NaF or amine fluoride, and saliva and 3-day-plaque-regrowth was collected at 5 time intervals during 6 hours after tooth brushing. The amount of collected saliva and plaque was measured, and the fluoride content was analysed using a fluoride sensitive electrode. All subjects repeated all study cycles 5 times, and 3 cycles per subject underwent statistical analysis using the Wilcoxon-Mann-Whitney test. Results Immediately after brushing the fluoride concentration in saliva increased rapidly and dropped to the baseline level after 360 minutes. No difference was found between NaF and amine fluoride. All plaque fluoride levels were elevated after 30 minutes until 120 minutes after tooth brushing, and decreasing after 360 minutes to baseline. According to the highly individual profile of fluoride in saliva and plaque, both levels of bioavailability correlated for the first 30 minutes, and the fluoride content of saliva and plaque was back to baseline after 6 hours. Conclusions Fluoride levels in saliva and plaque are interindividually highly variable. However, no significant difference in bioavailability between NaF and amine fluoride, in saliva, or in plaque was found.